Inhibition of Spirochaeta aurantia chemotaxis by neurotoxins. - Goulbourne, E A (1983)
The effects of neurotoxic compounds on the chemotactic response of Spirochaeta aurantia were investigated. In the presence of neurotoxins that affect action potential generation and transmission in excitable eucaryotic cells, D-xylose taxis was inhibited by 69 to 93%. Inhibition of chemotaxis was not due to decreased viability or motility. This study supports the hypothesis that the molecular basis for sensory signal transduction in S. aurantia involves ion fluxes across the cytoplasmic membrane.